Surface-attached sulfonamide containing quaternary ammonium antimicrobials for textiles and plastics. Issue 6 (23rd January 2019) - Caschera, Alexander; Mistry, Kamlesh B.; Bedard, Joseph; Ronan, Evan; Syed, Moiz A.; Khan, Aman U.; Lough, Alan J.; Wolfaardt, Gideon; Foucher, Daniel A.
Abstract : A series of surface attached silane or benzophenone sulfonamide quaternary ammonium antimicrobials show potent efficacy at solid/air and solid/liquid interfaces. Abstract : With the risks associated with healthcare-associated infections and the rise of antibiotic resistant microorganisms, there is an important need to control the proliferation of these factors in hospitals, retirement homes and other institutions. This work explores the development and application of a novel class of sulfonamide-based quaternary ammonium antimicrobial coatings, anchored to commercially and clinically relevant material surfaces. Synthesized in high yields (60–97%), benzophenone-anchored antimicrobials were spray-coated and UV grafted onto plastic surfaces, while silane-anchored variants were adhered to select textiles via dip-coating. Surface modified samples were characterised by advancing contact angle, anionic dye staining, X-ray photoelectron spectroscopy and atomic force microscopy. After verifying coating quality through the above characterization methods, microbiological testing was performed on batch samples in conditions that simulate the natural inoculation of surfaces and objects (solid/air) and water containers (solid/liquid). Using the previously established Large Drop Inoculum (LDI) protocol at solid/air interfaces, all treated samples showed a full reduction (10 5 –10 7 CFU) of viable Arthrobacter sp., S. aureus, and E. coli after 3 h of contact time. Additional testing of the walls of plastic LDPE vials treated with a UV-cured sulfonamide antimicrobial at a solid/liquid interface using the newly developed Large Reservoir Inoculum (LRI) protocol under static conditions revealed a complete kill (>10 6 reduction) of Gram-positive Arthrobacter sp., and a partial kill (>10 4 reduction) of Gram-negative E. coli within 24–48 h of contact.